EXTRA-CURIAL STATEMENTS BY A NON- TESTIFYING CO-ACCUSED, THE CANADIAN SUPREME COURT AND CHANGE IN SOUTH AFRICA - BC Naudé (Obiter, 2018)
In S v Ndhlovu (2002 (2) SACR 325 (SCA)), the court opened the door to the admissibility of extra-curial statements made by a non-testifying accused against a co-accused as hearsay in terms of section 3 of the Law of Evidence Amendment Act (45 of 1988), if the interests of justice so require. However, first the Supreme Court of Appeal and later the Constitutional Court rejected such an approach. It is beyond the scope of this comment to repeat the arguments in favour of a discretionary approach for such statements, but it is submitted that there is scope for disagreement with the findings of both courts. Whitear points out that the provisions dealing with the admissibility of hearsay in the Law of Evidence Amendment Act (45 of 1988) were not declared unconstitutional by any court. The Supreme Court of Appeal found that section 3 of the Law of Evidence Amendment Act (45 of 1988) could not be used to admit the extra-curial statement of an accused against his co- accused because the interests of justice would never allow this. The Constitutional Court found that section 3 did not override the common-law rule prohibiting the admission of extra-curial statements against a co- accused since this would amount to unfair discrimination against an accused implicated by such admissions or confessions. Significantly, because it is stated in section 3 of the Law of Evidence Amendment Act (45 of 1988) that section 3 is subject to the “provisions of any other law”, the court decided that the common-law prohibition should prevail. Previously, however, the Supreme Court of Appeal has held that the “other laws” referred to in the Law of Evidence Amendment Act (45 of 1988) are alternative ways for admitting hearsay, and do not preclude the admissibility of hearsay in terms of section 3, even where there is another law that prohibits it. The court also referred with approval to S v Ndhlovu (supra) where it was explained that the very purpose of section 3 of the Law of Evidence Amendment Act (45 of 1988) was to “supersede the excessive rigidity and inflexibility – and occasional absurdity – of the common law position” by allowing for the admission of hearsay when the interests of justice so require. The admissibility of out-of-court statements by an accused against a co- accused is also dealt with differently in the United Kingdom (our relevant common law) today. Section 114(1)(d) of the Criminal Justice Act of 2003 makes it possible to admit the out-of-court statement of an accused against a co-accused as hearsay. However, the court in R v Y (supra par 57−62) did mention that this does not mean such statements should routinely be admitted without a consideration of the relevant factors mentioned in the Criminal Justice Act of 2003 and that, in the majority of cases, it will not be in the interests of justice to admit such statements, especially those made during police interviews. Even though, under South African law, it is not currently possible to present evidence of an extra-curial statement made by an accused that also implicates a co-accused, the recent judgment by the Canadian Supreme Court in R v Bradshaw (2017 SCC 35) provides insight into how this could possibly happen in future. It is thus useful to consider the Supreme Court’s decision.